Draft Annual Plan 1988-89 Part-I: Summary of Sectoral Outlay and Statistical Statements Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1987)
Goa, Daman and Diu were constituted as a separate Union Territory in 1962 after their liberation from Portuguese regime on December 19, 1961. Earlier, the district of Daman is known to have formed part of the country known as 'Lata' which was one of the seven divisions of Konkan Vishaya between the second century B .C. to 13th century, A.L.. It was acquired by the Portuguese in 1559 from the Shah of Gujarat after having attacked many times. The documented history of Diu district begins with the rule of Mauriyas (C.322-220 E.C.) It was conquered by the Portuguese in 1546 from the Shah of Gujarat. In between the above periods, both Daman and Diu had a chequered history having been under the possession of and ruled by many king, and dynasties.
Union Territory of Daman and Diu, Directorate of Planning, Statistics and Evaluation